Role of meningococcal Neisserial autotransporter lipoprotein (NalP) in host pathogenesis - Dufailu, Osman Adamu (2017)
Neisseria meningitidis (Nm) can cause life-threatening bacterial meningitis and septicaemia. The high mortality of meningitis is associated with meningococcal invasion of the central nervous system (CNS) by breaching of the blood-brain barrier (BBB). Nm elaborates several cell-surface and secreted virulence factors that promote host invasion and colonisation. One important class are the autotransporter proteins. Adhesion and penetration protein (App), meningococcal serine protease A (MspA), Immunoglobulin A1 protease (IgA1p) and Neisserial autotransporter lipoprotein (NalP) are serine protease autotransporters of Nm; all have previously been demonstrated to have roles in meningococcal virulence. For App and MspA, uptake by host cells, nuclear localisation, histone clipping and induction of apoptosis have been described in our laboratory. However, a time course for the efficient uptake and nuclear localisation of these proteins into human brain microvascular endothelial cells (HBMECs) and details regarding the mechanism for histone clipping remained unknown. To address these points, both App and MspA and proteolytically-inactive mutant derivatives were expressed using the pColdTF vector system and purified under native conditions. Using confocal scanning microscopy optimal uptake and nuclear localisation of recombinant fusion proteins containing the functional passenger domains of both App and MspA in HBMECs was shown to occur 8 h-post exposure. Furthermore, the requirement for the active site serine residue in both autotransporters for H3.1 clipping was demonstrated, and human coagulation factor V (FV) was shown to be an additional substrate for both proteins.